Impact of performance and barriers towards Industrial Revolution 4.0 implementation in Malaysian construction projects / Nicole Wee Zhen Zhi ... [et al.] - Zhen Zhi, Nicole Wee; Low, Wai Wah; Wong, Shi Yee; Wong, Kwong Soon (Universiti Teknologi MARA, Perak, 2022)
Malaysian construction industry is still lagging in new technology adoption, while the world is moving towards Industrial Revolution 4.0 (IR 4.0). This study aims to identify the critical barriers of hindering the implementation of IR 4.0 among stakeholders in construction industry by using a set of questionnaires. The impacts of IR 4.0 to construction industry were also studied. The quantitative data were analysed using Relative Importance Index. The data revealed that the top barriers were related to technology deficiency and financial issue, while the greatest impacts of IR 4.0 implementation on project performance were safety, project success and time performance. The future of construction industry moving towards a fully digitalization is promising, although a longer time is required to achieve the desired status.